1993
DOI: 10.1210/jcem.77.5.8077337
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of recombinant human insulin-like growth factor I on bone turnover in normal women.

Abstract: Because insulin-like growth factor I (IGF-I) is a potent stimulator of osteoblast proliferation, it has potential in the treatment of osteoporosis. However, IGF-I affects multiple organ systems, and it is unclear whether treatment can stimulate bone formation without producing unacceptable side effects. Therefore, we evaluated the effects of treatment with recombinant human IGF-I in 18 postmenopausal women who received various dosages (30, 60, 120, or 180 micrograms/kg.day) by sc injections for 6 days. Serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 13 publications
4
48
0
Order By: Relevance
“…Deficiency in IGF1, a prominent member of IGFs, is suggested to be a cause of decrease in bone density with aging (20,21), and administration of IGF1 prevents the decrease of bone density in osteoporosis patients in part by stimulating osteogenesis (22)(23)(24). The high homology between IGF1 and insulin suggested that the osteogenesis-enhancing activity of IGF1 may be mimicked by the chemicals that potentiated the insulin-induced adipogenesis.…”
Section: Figmentioning
confidence: 99%
“…Deficiency in IGF1, a prominent member of IGFs, is suggested to be a cause of decrease in bone density with aging (20,21), and administration of IGF1 prevents the decrease of bone density in osteoporosis patients in part by stimulating osteogenesis (22)(23)(24). The high homology between IGF1 and insulin suggested that the osteogenesis-enhancing activity of IGF1 may be mimicked by the chemicals that potentiated the insulin-induced adipogenesis.…”
Section: Figmentioning
confidence: 99%
“…However, both authors also determined nearly similar osteoinductive effects of TGF-β1 in a wide range of concentrations [13,39]. Additionally, Ebeling et al [10] demonstrated analogous effects of four different doses of IGF-I on bone turnover in normal women. Although dose-dependent effects for isolated IGF-I and TGF-β1 application are sufficiently documented, to our knowledge, no study has been performed to determine whether a dose-dependent effect of combined IGF-I and TGF-β1 application on bone matrix formation exists.…”
Section: Fluorochrome Analysis Resultsmentioning
confidence: 93%
“…Information on the effects of growth factor therapy on older people is limited to that from two studies using rhIGF-I. The results with low-dose rhIGF-I reported by Ebeling et al [31] and Ghiron et al [37] provided biochemical evidence for increased bone formation activity with minimal increased resorption. However, the effects of rhIGF-I and rhTGF␤ on bone mass and fracture occurrence in older people have not yet been reported nor have optimal dosage schedules been established.…”
Section: Resultsmentioning
confidence: 99%
“…In a study involving 18 postmenopausal women (mean age 66 years), Ebeling et al evaluated the effects of various dosages of subcutaneous rhIGF-I (30, 60, 120 or 180 g/kg/day) for 6 days [31]. Serum IGF-I concentrations increased two-to fourfold during treatment.…”
Section: In Vivo Effects Of Rhigf-imentioning
confidence: 99%